2022
DOI: 10.3390/biomedicines10112702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of 3D-Printed Bioresorbable Scaffolds for Bone Tissue Engineering—A Pilot Study on 126 Patients for Burrhole Covers in Subdural Hematoma

Abstract: Burrhole craniostomy is commonly performed for subdural hematoma (SDH) evacuation, but residual scalp depressions are often cosmetically suboptimal for patients. OsteoplugTM, a bioresorbable polycaprolactone burrhole cover, was introduced by the National University Hospital, Singapore, in 2006 to cover these defects, allowing osseous integration and vascular ingrowth. However, the cosmetic and safety outcomes of OsteoplugTM-C—the latest (2017) iteration, with a chamfered hole for subdural drains—remain unexplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…At present, it is much accounted of biological materials in tissue repairing and many of them are FDA-approved for clinical conversion like 3D-print polycaprolactone scaffold [ 43 ], such as Osteoplug TM proven to be safe over a 10-year period for craniotomy burr hole reconstruction [ 44 ] and reducing scalp-depression-related cosmetic handicaps in patients [ 45 ]. However, in orthopedics, bone repair cannot be achieved with biological scaffolds alone, which often need to be combined with other related drugs or biological components to achieve therapeutic effects, like β-TCP [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, it is much accounted of biological materials in tissue repairing and many of them are FDA-approved for clinical conversion like 3D-print polycaprolactone scaffold [ 43 ], such as Osteoplug TM proven to be safe over a 10-year period for craniotomy burr hole reconstruction [ 44 ] and reducing scalp-depression-related cosmetic handicaps in patients [ 45 ]. However, in orthopedics, bone repair cannot be achieved with biological scaffolds alone, which often need to be combined with other related drugs or biological components to achieve therapeutic effects, like β-TCP [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another study reported 12 cases of uneventful burr hole reconstruction, observing simultaneous progressive bone regeneration [102]. Recent publications have noted that the use of PCL plugs resulted in effective bone regeneration after ~1 year (see Figure 4D) and significantly higher scores for both aesthetic outcomes and quality of life (QOL) without an increase in complication rates in comparison to patients with untreated burr holes who suffered from scalp depression [103,104].…”
Section: Three-dimensional-printed Pcl and Its Compositesmentioning
confidence: 95%
“…From an engineering point of view, one of the main challenges in developing TE scaffolds is optimizing the scaffold design to meet biological requirements. It includes considering the ability to support cell seeding, cell differentiation, cell proliferation, and vascularization [6][7][8][9][10]. Therefore, an essential parameter in designing a scaffold must take into account the histomorphometric characteristics of the scaffold so that the requirements mentioned above can be met.…”
Section: Introductionmentioning
confidence: 99%